Yield Stability and Quality of Wheat (Triticum spp.) and Barley (Hordeum Vulgare) Populations Evolving under Different Microenvironments: A review - Al-Khatib, Amal; Kafawin , Omar; Grando , Stefania (Jordan Journal of Agricultural Sciences, 2023)
Climate change, human population growth, human health and food security, safety, and sovereignty all demand that the role of biodiversity in plant breeding be revisited. From a biological standpoint, it is possible that populations of diverse plants developed by evolutionary plant breeding will be able to handle the majority of these major issues. Water stress and soil nutrient deficiency may have a negative impact on wheat (Triticum spp.) and barley (Hordeum vulgare) yields and qualities. Drought-tolerant wheat cultivars with high yield and quality potential and improved grain protein content must be developed if food security is to be maintained. Wheat and barley (Triticum spp. and Hordeum vulgare, respectively) are the focus of this research, which aims to examine the stability of evolutionary populations (EPs) in the face of stressful and changeable settings. It's also important to look at how evolved populations stack up against improved varieties in terms of yield and its components. There has not been much progress in making wheat and barley more resistant to drought, especially in Jordan, where the problem is felt the most.